Fast Determination of Furocoumarins in Food Supplements Containing Heracleum sphondylium L. Using Capillary Electrophoresis - Eszter Laczkó Zöld; Csenge Kis; Erzsébet Nagy-György; Erzsébet Domokos; Elek Ferencz; Zoltán-István Szabó (Foods)
Hercaleum sphondylium L., commonly known as hogweed, is a plant species that has been employed as an ingredient in food supplements aimed at enhancing reproductive organ functionality, restoring hormonal equilibrium, and producing an aphrodisiac effect. Importantly, the European Food Safety Authority (EFSA) has designated it as a “substance of possible concern for human health” when found in food and food supplements, as detailed in the EFSA compendium of botanicals. Given the potential health consequences associated with the ingestion of furocoumarin-containing plants, the primary objective of this study was to develop a straightforward and rapid method for screening various furocoumarins (bergapten, isobergapten, isopimpinellin, imperatorin, and xanthotoxin) that are found in hogweed plant products and hogweed-derived food supplements. A novel ultrafast micellar electrokinetic chromatographic method was established, achieving analysis durations of less than 3 min for the complete separation of the analytes. This method is additionally characterized by its simplicity, allowing for the analysis of samples following a rapid extraction procedure and dilution, without necessitating extra cleanup steps. The investigation of ten food supplements indicated that seven products contained no detectable levels of furocoumarins, one product presented levels close to the harmless threshold, and two products exhibited concentrations significantly exceeding this threshold. The results of this study illustrate the potential of micellar electrokinetic chromatography as a feasible alternative technique for the analysis of furocoumarins in herbal products and food supplements.